2013
DOI: 10.1371/journal.pone.0069845
|View full text |Cite
|
Sign up to set email alerts
|

Is Ritonavir-Boosted Atazanavir a Risk for Cholelithiasis Compared to Other Protease Inhibitors?

Abstract: ObjectiveTo compare the incidence of complicated cholelithiasis in patients receiving ritonavir-boosted atazanavir (ATV/r)- containing antiretroviral therapy with those on other protease inhibitors (PIs).DesignWe conducted a single-center retrospective cohort study of patients who started either ritonavir-boosted ATV/r- or other PIs (ritonavir-boosted fosamprenavir, unboosted fosamprenavir, lopinavir/ritonavir, and ritonavir-boosted darunavir) -containing antiretroviral therapy.MethodsThe incidence of complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…The potential association between exposure to ATV and increased risk to cholelithiasis is still a matter of debate. Indeed, Hamada and co-workers reported a low incidence of complicated cholelitiasis in patients on ATV comparable to other PIs [ 30 ]. These results have been partially challenged by recent findings from the same authors [ 31 ] reporting an increased risk of cholelithiasis in patients treated with ATV for more than two years.…”
Section: Discussionmentioning
confidence: 96%
“…The potential association between exposure to ATV and increased risk to cholelithiasis is still a matter of debate. Indeed, Hamada and co-workers reported a low incidence of complicated cholelitiasis in patients on ATV comparable to other PIs [ 30 ]. These results have been partially challenged by recent findings from the same authors [ 31 ] reporting an increased risk of cholelithiasis in patients treated with ATV for more than two years.…”
Section: Discussionmentioning
confidence: 96%
“…In line with these findings, a retrospective observational study of fourteen patients treated with ATV who had developed complicated cholelithiasis reported that in four patients, 100% of the biliary calculi was made up of ATV [65]. Incidence of cholelithiasis has not been found to differ between patients treated with ATV/r and those treated with other protease inhibitors boosted with ritonavir [66]. One retrospective pharmacogenetic study of 910 HIV-positive individuals who had undergone therapeutic drug monitoring and abdominal sonography reported no association between either UGT1A1 *28 or rs2032582 (c. c.2677 A>C/T) in ABCB1 (also known as MDR1 2677A>C/T) with risk of cholelithiasis [7].…”
Section: Pharmacogenomics Of Atv/rmentioning
confidence: 88%
“…Atazanavir has an increased risk of developing galland kidney stones over time [38,39] and icterus due to inhibition of the enzyme UGT1A is a common adverse effect. Another disadvantage of atazanavir is the decreased absorption seen in increasing pH, which means atazanavir should not be combined with proton pump inhibitors.…”
Section: Rationale For Recommendationmentioning
confidence: 99%